The regulation of the Malaysian futures industry / Martin Dearmer Cross - Martin, Dearmer Cross (1999)
This thesis makes a study of the regulation of the Malaysian futures industry. It seeks to provide an overview, analysis and critique of the legislative and regulatory system under which the Malaysian futures industry operates. An attempt is made to highlight the effectiveness of that system, both in the light of past achievement and of anticipated future performance. Reference has been made where necessary to other jurisdictions.